Transformation Of The Concept Of Khidmah In Pesantren Al-Munawwir Krapyak Yogyakarta - Fathurrohman, Rizal; Arifi, Ahmad (Nadwa: Jurnal Pendidikan Islam, 2024)
The concept of khidmah has expanded in Pesantren, seeing that today's Kiai have various social positions, such as political Kiai, business Kiai, academic Kiai, and so on. This study aims to describe the actualization of the concept of khidmah santri towards Kiai in Pesantren. This study used a qualitative method with the concept of khidmah in Pesantren as the research object. Data were collected from key informants such as clerics, ustadz, santri, and Pesantren administrators who were selected by purposive sampling, using documentation study, observation, and interview methods. The findings of this research indicate that there has been a transformation of the concept of khidmah in Islamic boarding schools which can be actualized in several concepts. 1) the concept of khidmah towards special Kiai (teaching Kiai) by becoming abdi ndalem, badal, and chauffeurs of the Kiai. 2) the concept of khidmah towards business clerics in an employee-like manner. 3) the concept of khidmah towards academic Kiai by becoming badal Kiai. 4) the concept of service to the political Kiai by serving as a Kiai Pesantren staff member and personal assistant to the Kiai